Intranasal dexmedetomidine, as midazolam-sparing drug, for MRI in preterm neonates. - Bua, Jenny; Massaro, Marta; Cossovel, Francesca; Monasta, Lorenzo; Brovedani, Pierpaolo; Cozzi, Giorgio; Barbi, Egidio; Demarini, Sergio; Travan, Laura (Paediatr Anaesth, 2018)

Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature. - Travan, Laura; Naviglio, Samuele; De Cunto, Angela; Pellegrin, Andrea; Pecile, Vanna; Spinelli, Alessandro Mauro; Cappellani, Stefania; Faletra, Flavio (Am J Med Genet A, 2017)
The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were reviewed and compared to our patient, highlighting the common features of a possible 19q13.32 microdeletion syndrome.

Presentation of acute suppurative parotitis in a newborn with incessant crying. - Velkoski, Angelika; Amoroso, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Trappan, Antonella; Travan, Laura (Arch Dis Child Fetal Neonatal Ed, 2017)
Keywords: Acute Disease; Anti-Bacterial Agents; Crying; Female; Humans; Infant, Newborn; Parotitis; Staphylococcal Infections; Staphylococcus aureus

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

Cerebral oxygenation with different nasal continuous positive airway pressure levels in preterm infants. - Bembich, Stefano; Travan, Laura; Cont, Gabriele; Bua, Jenny; Strajn, Tamara; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2015)
OBJECTIVES: This study evaluates the effect of varying nasal continuous positive airway pressure (NCPAP) level on cerebral blood flow (CBF) and oxygenation in preterm infants. METHODS: Oxy-haemoglobin (HbO2) and total haemoglobin (HbTot), as CBF estimates, and the ratio between HbO2 and HbTot (HbO2/HbTot), as cerebral oxygenation estimate, were assessed by near-infrared spectroscopy in 26 stable preterm newborns at a postmenstrual age between 26 and 33 weeks. Baseline HbO2, HbTot and HbO2/HbTot values were initially collected with NCPAP at 5 cm H2O and then compared with values obtained with NCPAP levels at both 3 and 8 cm H2O. RESULTS: Compared with 5 cm H2O, cerebral HbO2, HbTot and HbO2/HbTot remained unchanged both after increasing (to 8 cm H2O) and decreasing (to 3 cm H2O) the NCPAP level. This result was observed both in regional areas (24 sites) and in the overall monitored area (frontal and parietal cortex). Compared with 8 cm H2O, peripheral oxygen saturation significantly decreased at 3 cm H2O (p=0.021). Heart rate did not change. CONCLUSIONS: No differences in CBF and cerebral oxygenation were observed with NCPAP levels in the range 3-8 cm H2O despite a decrease in peripheral oxygenation with 3 cm H2O.
Keywords: Cerebrovascular Circulation; Continuous Positive Airway Pressure; Female; Hemoglobins; Humans; Infant, Newborn; Infant, Premature; Intensive Care, Neonatal; Male; Nasal Cavity; Oxygen; Oxygen Consumption; Oxyhemoglobins; Spectroscopy, Near-Infrared

Impact of Surgery for Neonatal Gastrointestinal Diseases on Weight and Fat Mass. - De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (J Pediatr, 2015)
OBJECTIVE: To compare growth, fat mass (FM), and fat-free mass in surgical infants vs matched controls at similar postconceptional age (PCA). STUDY DESIGN: Anthropometric and body composition measurements by air-displacement plethysmography (PeaPod-Infant Body Composition System; LMI, Concord, California) were performed at the same PCA in 21 infants who received gastrointestinal surgery and in 21 controls matched for gestational age, birth weight, and sex. RESULTS: Despite similar anthropometry at birth, postsurgical infants were shorter (50.4 [4.7] cm vs 53.2 [4.1] cm, P = .001), lighter (3516 [743] g vs 3946 [874] g, P < .001), and had lower FM content (%FM 14.8 [4.7]% vs 20.2 [5.8]%, P < .0001) than their peers at similar PCA (43 [4] weeks). All surgical infants but 1 (20/21) received parenteral nutrition (PN). Mean PN duration was 40 (30) days. Five infants in the control group received PN because of prematurity for 15 (9-30) days. Nine infants in the surgical group and 1 in the control group had PN-associated cholestasis. CONCLUSIONS: Neonates having surgery for gastrointestinal diseases were shorter, had lower weight, and lower FM content than their peers, despite receiving more PN. Body composition evaluation and monitoring may help optimize growth in these newborns.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

More than (Double) Bubble. - Ferrara, Giovanna; Stampalija, Tamara; Codrich, Daniela; Simionato, Cristina; Taddio, Andrea; Travan, Laura (J Pediatr, 2015)
Keywords: Amniotic Fluid; Duodenum; Female; Humans; Infant; Infant, Newborn; Polyhydramnios; Pregnancy; Pregnancy Trimester, Third; Prenatal Diagnosis; Ultrasonography, Prenatal

Pain activates a defined area of the somatosensory and motor cortex in newborn infants. - Bembich, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Travan, Laura; Grassi, Veronica; Demarini, Sergio (Acta Paediatr, 2015)

Risk-adjusted operative delivery rates and maternal-neonatal outcomes as measures of quality assessment in obstetric care: a multicenter prospective study. - Maso, Gianpaolo; Monasta, Lorenzo; Piccoli, Monica; Ronfani, Luca; Montico, Marcella; De Seta, Francesco; Parolin, Sara; Businelli, Caterina; Travan, Laura; Alberico, Salvatore (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Although the evaluation of caesarean delivery rates has been suggested as one of the most important indicators of quality in obstetrics, it has been criticized because of its controversial ability to capture maternal and neonatal outcomes. In an "ideal" process of labor and delivery auditing, both caesarean (CD) and assisted vaginal delivery (AVD) rates should be considered because both of them may be associated with an increased risk of complications. The aim of our study was to evaluate maternal and neonatal outcomes according to the outlier status for case-mix adjusted CD and AVD rates in the same obstetric population. METHODS: Standardized data on 15,189 deliveries from 11 centers were prospectively collected. Multiple logistic regression was used to estimate the risk-adjusted probability of a woman in each center having an AVD or a CD. Centers were classified as "above", "below", or "within" the expected rates by considering the observed-to-expected rates and the 95% confidence interval around the ratio. Adjusted maternal and neonatal outcomes were compared among the three groupings. RESULTS: Centers classified as "above" or "below" the expected CD rates had, in both cases, higher adjusted incidence of composite maternal (2.97%, 4.69%, 3.90% for "within", "above" and "below", respectively; p = 0.000) and neonatal complications (3.85%, 9.66%, 6.29% for "within", "above" and "below", respectively; p = 0.000) than centers "within" CD expected rates. Centers with AVD rates above and below the expected showed poorer and better composite maternal (3.96%, 4.61%, 2.97% for "within", "above" and "below", respectively; p = 0.000) and neonatal (6.52%, 9.77%, 3.52% for "within", "above" and "below", respectively; p = 0.000) outcomes respectively than centers with "within" AVD rates. CONCLUSIONS: Both risk-adjusted CD and AVD delivery rates should be considered to assess the level of obstetric care. In this context, both higher and lower-than-expected rates of CD and "above" AVD rates are significantly associated with increased risk of complications, whereas the "below" status for AVD showed a "protective" effect on maternal and neonatal outcomes.

When Feeding Difficulties Are due to Genetics: The Case of Familial Partial 9q Duplication. - Travan, Laura; Rocca, Maria Santa; Buonomo, Francesca; Cleva, Lisa; Pecile, Vanna; De Cunto, Angela (J Investig Med High Impact Case Rep, 2015)
Chromosomal abnormalities may cause growth failure before or since birth. 9q duplication is reported as a cause of intrauterine growth restriction, mild dysmporphism, and intellectual disabilities. We report a case of a maternally inherited 9q21.31q21.33 duplication causing prenatal and postnatal growth restriction with feeding refusal and mild facial dysmorphisms, prenatally diagnosed by single-nucleotide polymorphism array analysis. Hypothesis of the possible pathogenic mechanisms are discussed.

Can body mass index accurately predict adiposity in newborns? - De Cunto, Angela; Paviotti, Giulia; Ronfani, Luca; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2014)
Body mass index (BMI) is correlated with body fatness and risk of related diseases in children and adults. Proportionality indexes such as BMI and ponderal index (PI) have been suggested as complementary measures in neonatal growth assessment. Yet, they are still not used in neonates and their correlation with fatness is unknown. The aim of the study was to test the hypothesis that BMI z-score would predict neonatal adiposity. Body composition measurements (ie, fat mass, fat-free mass) by air displacement plethysmography (PEA POD, LMI, Concord-USA), weight and length were obtained in 200 infants ≥36 weeks' gestational age (GA) at birth. Linear regression analysis showed a direct association between BMI z-score and %fat mass (r(2)=0.43, p<0.0001). This association was confirmed independently from sex, GA and maternal prepregnancy BMI. BMI z-score predicted adiposity better than PI. However, both BMI z-score and PI were poor predictors of adiposity at birth.
Keywords: Adiposity; Adult; Anthropometry; Body Composition; Body Mass Index; Cross-Sectional Studies; Female; Gestational Age; Humans; Infant, Newborn; Male; Mothers; Plethysmography; Predictive Value of Tests; Regression Analysis; Reproducibility of Results; Sex Factors

High-frequency percussive ventilation as rescue treatment in severe hypoxemic respiratory failure in term neonates. - Paviotti, Giulia; Bua, Jenny; De Cunto, Angela; Travan, Laura; Demarini, Sergio (J Crit Care, 2014)
Keywords: Female; High-Frequency Ventilation; Humans; Male; Oxygen; Pulmonary Gas Exchange; Respiratory Insufficiency

Severe neonatal hyperbilirubinemia and UGT1A1 promoter polymorphism. - Travan, Laura; Lega, Sara; Crovella, Sergio; Montico, Marcella; Panontin, Elisa; Demarini, Sergio (J Pediatr, 2014)
OBJECTIVE: To assess whether UGT1A1 promoter polymorphisms associated with Gilbert Syndrome (GS) occur with a greater frequency in neonates with severe hyperbilirubinemia. STUDY DESIGN: In a case-control study performed at a single hospital center in Italy, 70 case subjects with severe hyperbilirubinemia (defined as bilirubin level ≥20 mg/dL or 340 μmol/L) and 70 controls (bilirubin level <12 mg/dL or 210 μmol/L) were enrolled. Both case and control subjects were full term newborns. Polymerase chain reaction analysis on blood spot was performed to determine the frequency of UGTA1A1 promoter polymorphisms in cases and controls. RESULTS: No statistical difference in the prevalence of UGTA1A1 gene variants was found between cases and controls (P = 1). Thirteen infants homozygous for (TA)7 polymorphism associated with GS were in the case group (18.6%) and 14 in the control group (20.0%). A heterozygous group was also equally distributed between cases (44.3%) and controls (42.9%). No (TA)8 repeat was found in the 2 groups. CONCLUSIONS: In our study population, GS polymorphism alone does not appear to play a major role in severe neonatal hyperbilirubinemia in neonates without signs of hemolysis.
Keywords: Case-Control Studies; Female; Genotype; Gilbert Disease; Glucuronosyltransferase; Humans; Hyperbilirubinemia, Neonatal; Infant, Newborn; Male; Polymerase Chain Reaction; Polymorphism, Genetic; Prevalence; Promoter Regions, Genetic

Congenital hemangiopericytoma. - Travan, Laura; Demarini, Sergio; Del Frate, Giovanni; Zacchi, Alberto (J Pediatr, 2012)
Keywords: Biopsy, Needle; Female; Gestational Age; Hemangiopericytoma; Humans; Immunohistochemistry; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prognosis; Risk Assessment; Soft Tissue Neoplasms; Treatment Outcome; Ultrasonography, Prenatal

Effects of prone and supine position on cerebral blood flow in preterm infants. - Bembich, Stefano; Oretti, Chiara; Travan, Laura; Clarici, Andrea; Massaccesi, Stefano; Demarini, Sergio (J Pediatr, 2012)
We evaluated the effect of prone and supine position on cerebral blood flow (CBF) in stable preterm infants. CBF, PO(2), and PCO(2) were measured in the two positions. Peripheral oxygenation increased and CBF decreased in prone position. We speculate that CBF autoregulation may compensate for increased peripheral oxygenation, by decreasing CBF.
Keywords: Cerebrovascular Circulation; Female; Humans; Infant, Newborn; Infant, Premature; Male; Prone Position; Regional Blood Flow; Supine Position

Managing children under 36 months of age with febrile urinary tract infection: a new approach. - Pennesi, Marco; L'erario, Ines; Travan, Laura; Ventura, Alessandro (Pediatr Nephrol, 2012)
BACKGROUND: Recent guidelines on urinary tract infection (UTI) agree on reducing the number of invasive procedures. None of these has been validated by a long-term study. We describe our 11-years experience in the application of a diagnostic protocol that uses a reduced number of invasive procedures. METHODS: We reviewed retrospectively the records of 406 children aged between 1 and 36 months at their first UTI. All patients underwent renal ultrasound (RUS). Children with abnormal RUS and those with UTI recurrences underwent voiding cystourethrography (VCUG) and dimercaptosuccinic acid (DMSA) renal scans. RESULTS: RUS after the first UTI was pathological in 7.4% children; 4.4 % had a second UTI. We performed 48 VCUG: 14 patients (29%) had vesicoureteral reflux (VUR), 12 of which showed an abnormal RUS while 2 had recurrent UTI. After DMSA renal scan renal damage appeared in only 6 of them (12.5%); all these children showed grade IV VUR. CONCLUSIONS: The application of our guidelines leads to a decrease in invasive examinations without missing any useful diagnoses or compromising the child's health.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Humans; Infant; Male; Pediatrics; Recurrence; Retrospective Studies; Urinary Tract Infections

Storage of human milk: accepting certain uncertainties. - Davanzo, Riccardo; Travan, Laura; Demarini, Sergio (J Hum Lact, 2010)
Keywords: Food Handling; Humans; Milk, Human; Refrigeration